An investigation of the impact of experimental colitis and inflammatory bowel disease on behaviour and on systemic and central inflammation - Abautret-Daly, Áine (Trinity College (Dublin, Ireland). School of Pharmacy & Pharmaceutical Sciences, 2013)
Inflammatory bowel diseases (IBD) are chronic conditions characterised by uncontrolled inflanmiation of the intestinal mucosa. Clinical symptoms include weight loss, diarrhoea, rectal bleeding and abdominal pain. In addition to physical symptoms, patients with IBD are at increased risk of depression and anxiety. Whether these psychological disturbances occur due to stress associated with the unpleasant symptoms of IBD, or as a result of biological mediators of inflammation is unknown. It has been suggested that pro-inflammatory cytokines themselves can induce mood changes, or that cytokines (particularly interferon γ (IFNγ)) can induce depression and anxiety by degrading tryptophan to kynurenine via induction of indolaniine 2,3 dioxygenase (IDO). In addition, tryptophan can be metabolised to kynurenine via tryptophan 2,3 dioxygenase (TDO). The main aim of this thesis was to investigate the association between colonic inflammation or IBD symptoms and mood/anxiety disturbances in patients, and to examine the implications of colonic inflanunation on central markers of immune activation in animal models of colitis. 18 IBD patients and 19 patient controls were scored using the Hamilton-depression (HAM-D), HAM-anxiety (HAM-A), profile of mood states (POMS), and disease activity scores (Inflammatory bowel disease questionnaire, Mayo index, and Crohn’s disease activity index). Intestinal biopsies were analysed by PCR for interleukin-6 (IL-6), IL-1β, tumor necrosis factor TNFα, inducible nitric oxide synthase (iNOS), IFNγ, IDO, and matrix metalloproteases 9 (MMP9). Whole blood PAXgene analysis of IFNγ, IDO, MMP9, and iNOS was examined by PCR. Circulating concentrations of IL-6, IFNγ, and C-reactive protein (CRP) w'ere analysed by ELISA, and kynurenine and tryptophan concentrations were examined by High performance liquid chromatography (HPLC). A significant increase in HAM-D scores was found, which was independent of the psychological impact of acute symptoms, but was associated with increased colonic and circulating cytokine expression and kynurenine:tryptophan ratio.
Keywords: Pharmacy & Pharmaceutical Sciences, Ph.D.; Ph.D. Trinity College Dublin